Bauhinia proboscidea (Fabaceae: Cercidoideae), a new species from Costa Rica and Panama, with notes on B. beguinotii, B. gorgonae and B. pansamalana - Juárez Retana, Pedro (2018)
Bauhinia proboscidea, a new species from Costa Rica and Panama, is described and illustrated, and compared to the closely related B. pansamalana of southern Mexico, Guatemala and Honduras. It is also compared with B. beguinotii, with which has been confused in herbaria. Bauhinia gorgonae, endemic to Gorgona Island in Colombia and which has been classified as a variety of B. beguinotii, is here considered a separate species. A key to the Neotropical species of Bauhinia with three fertile stamens is provided. Some observations on the morphology and reproductive biology of B. proboscidea are presented. Global-level assessments of the conservation status according to IUCN Red List criteria indicate that B. proboscidea and B. beguinotii (which was previously assessed using some misidentified records) should both be considered as species of Least Concern (LC), B. gorgonae should be considered as Endangered (EN), and B. pansamalana should be considered Not Threatened (NT). Country-level conservation assessments are also provided for all four species. The homology of the “intrastipular spines” of Bauhinia is briefly discussed.